Current management of trimalleolar ankle fractures. Issue 8 (10th August 2021) - Pflüger, Patrick; Braun, Karl-Friedrich; Mair, Olivia; Kirchhoff, Chlodwig; Biberthaler, Peter; Crönlein, Moritz
Abstract : A trimalleolar ankle fracture is considered unstable and treatment is generally performed operatively. Computed tomography is important for the operative planning by providing an elaborated view of the posterior malleolus. Trimalleolar ankle fractures have a rising incidence in the last decade with up to 40 per 100, 000 people per year. With a growing number of elderly patients, trimalleolar ankle injuries will become more relevant in the form of fragility fractures, posing a particular challenge for trauma surgeons. In patients with osteoporotic trimalleolar ankle fractures and relevant concomitant conditions, further evidence is awaited to specify indications for open reduction and internal fixation or primary transfixation of the ankle joint. In younger, more demanding patients, arthroscopic-assisted surgery might improve the outcome, but future research is required to identify patients who will benefit from assisted surgical care. This review considers current scientific findings regarding all three malleoli to understand the complexity of trimalleolar ankle injuries and provide the reader with an overview of treatment strategies and research, as well as future perspectives. Cite this article: EFORT Open Rev 2021;6:692-703. DOI: 10.1302/2058-5241.6.200138